Jihad Gender: Aplikasi Hermeneutika Pembebasan Farid Esack Dalam Menangani Kasus Kekerasan Seksual di Indonesia - Renci, Renci; Ramadhan, An-Najmi Fikri; Faizah, Thoriqotul (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
The case of sexual violence against women has sharply increased during the COVID-19 pandemic. Discourses on justice and gender equality have been extensively voiced by Muslim feminists to combat sexual violence against women. The aim of this research is to explicate the liberation hermeneutics advocated by Farid Esack as a foundation for practical realization of gender equality in cases of sexual violence. Farid Esack's hermeneutics seeks to engage in dialogue and bridge the gap between the text of the Qur'an and the context in which its verses are understood, which are then interpreted progressively to become drivers of anti-oppression spirit against women. This study employs a literature review methodology with qualitative analysis, utilizing an analytical-historical approach to data presentation. Furthermore, the collected data are analyzed through the key theoretical approach of Farid Esack's hermeneutics, particularly focusing on the keys of jihad, and then elaborated within the context of the struggle for gender equality in Indonesia. The results reveal that the concepts of gender equality in the Qur'an give rise to various action-practice measures in addressing cases of sexual violence in Indonesia: Firstly, male feminist activists are engaged in advocating for gender justice in addressing cases of sexual violence against women. Secondly, efforts are made to enact laws as legal frameworks governing policies to protect women from cases of sexual violence, such as the Sexual Violence Criminal Act (UU-TPKS) along with its derivative laws and supervision. Thirdly, the role of women's protection advocacy institutions accompanies victims of sexual violence, providing support for their recovery and ensuring their legal rights to be protected. Keywords: Hermeneutics, Gender Jihad, Sexual Violence